2020
DOI: 10.1186/s12052-020-00133-9
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling evolution: evidence from a biology and theology course

Abstract: Background: Many individuals reject evolutionary theory due to a perceived conflict with their religious beliefs. To bridge this gap, educators have attempted different approaches including approaching evolution rejection as a consequence of deficit thinking and teaching students the nature of science (including the scientific process and peer review process as well as questions that science can and cannot answer).Teaching the nature of science has shown promising gains in the acceptance of evolution, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…A way that evolution instructors may be able to reduce students' perceived conflict between evolution and belief in God is to discuss that evolution is not necessarily atheistic and that students do not have to reject a belief in God in order to accept evolution. Biologists and science education researchers have written extensively about the conflation of evolution acceptance with atheism (Smith, 1994;Miller, 1999;Meadows et al, 2000;Scott, 2005;Collins, 2006;Reiss, 2009;Gould, 2011;Southerland and Scharmann, 2013;Tolman et al, 2020). In our past study, we reported that almost half of college biology students think that in order to accept evolution they would have to be atheists, highlighting the prevalence of this misconception (Barnes et al, 2020a).…”
Section: Discussionmentioning
confidence: 83%
“…A way that evolution instructors may be able to reduce students' perceived conflict between evolution and belief in God is to discuss that evolution is not necessarily atheistic and that students do not have to reject a belief in God in order to accept evolution. Biologists and science education researchers have written extensively about the conflation of evolution acceptance with atheism (Smith, 1994;Miller, 1999;Meadows et al, 2000;Scott, 2005;Collins, 2006;Reiss, 2009;Gould, 2011;Southerland and Scharmann, 2013;Tolman et al, 2020). In our past study, we reported that almost half of college biology students think that in order to accept evolution they would have to be atheists, highlighting the prevalence of this misconception (Barnes et al, 2020a).…”
Section: Discussionmentioning
confidence: 83%
“…Those faculty that are religious, or are teaching at a religious institution, also have the potential to be role models that provide a pathway for religious students to accept evolution, a factor known to lead to greater acceptance of evolutionary theory (Holt et al 2018). Additionally, instructors at religiously affiliated institutions have the added benefit of being in the position to employ religious cultural competence in evolution education (ReCCEE), an important part of the reconciliatory approach known to lead to gains in undergraduate acceptance of evolution (Barnes and Brownell 2016;Lindsay et al 2019;Tolman et al 2020). Despite their advantageous position, many professors are not comfortable employing strategies such as a reconciliatory approach, or do not feel that it is their purpose to help their students accept evolution (Barnes and Brownell 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, there is an ample amount of literature demonstrating that faculty can address student fear surrounding evolution (Manwaring et al 2015;Barnes and Brownell 2016;Lindsay et al 2019;Tolman et al 2020;Barnes and Brownell 2017;Truong et al 2018;Bertka et al 2019), and can increase student knowledge of evolutionary theory (Sinatra et al 2003;Mead et al 2017;Walter et al 2013;Rios et al 2015;Dunk et al 2019), which account for many of the reported internal factors.…”
Section: Internal Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning about the mechanisms and evidence for evolution appears to be important for students' understanding of the theory of evolution and for changing students' minds about evolution. One study by Talbot et al (Talbot et al 2020), looked at biology majors taking their capstone evolution course and found that increased knowledge of the mechanisms and evidence for evolution was the most important factor for students' increasing their acceptance of evolution while completing their coursework. In other studies, there was no correlation between teaching the facts of evolution and acceptance of evolution (Bishop and Anderson 1990;Sinatra et al 2003;Brem et al 2003;Mead et al 2017).…”
Section: Influencers Of Evolution Acceptancementioning
confidence: 99%